2022
DOI: 10.1002/cncy.22632
|View full text |Cite
|
Sign up to set email alerts
|

Utility of NR4A3 on FNA cytology smears and liquid‐based preparations of salivary gland

Abstract: BACKGROUND: Fine-needle aspiration cytology (FNAC) is generally the initial sampling method for salivary gland neoplasms.The cytomorphologic features of acinic cell carcinoma (AciCC) of salivary gland can overlap with other neoplastic and nonneoplastic entities. AciCCs harbor a recurrent t(4;9) rearrangement with upregulation of nuclear receptor subfamily 4 group A member 3 (NR4A3). NR4A3 protein overexpression has been shown to be highly sensitive and specific for the diagnosis of AciCC in histologic specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…DOG1), a molecularly based IHC marker is now available for replacing molecular detection of ETV6::NTRK3 fusion [24][25][26][27]. Even acinic cell carcinoma is diagnosed by immunopositivity for NR4A3 [28][29][30][31] without establishing fusion script. Similarly, ETV4 [32] suffices to diagnose CICrearranged sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…DOG1), a molecularly based IHC marker is now available for replacing molecular detection of ETV6::NTRK3 fusion [24][25][26][27]. Even acinic cell carcinoma is diagnosed by immunopositivity for NR4A3 [28][29][30][31] without establishing fusion script. Similarly, ETV4 [32] suffices to diagnose CICrearranged sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…Salivary carcinomas are a heterogeneous group of tumors with few neoplasms that are molecularly labeled [9]. Acinic cell carcinoma is characterized by the presence of tumor cells with serous acinar cell differentiation for which the transcription factors NOR1 (also known as NR4A3) and Nurr1 (also known as NR4A2) have been identified as diagnostic markers, showing strong nuclear immunoreactivity [10][11][12]. Adenoid cystic carcinoma (AdCC) is a distinctive subtype characterized by its cribriform or tubular growth pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Skaugen et al demonstrated that NR4A3 immunostaining is negative in normal acini, which easily solved the diagnostic dilemma. [25][26][27] NR4A3 immunostaining is particularly helpful when the specimen has low cellularity insufficient for molecular diagnosis. It serves as an important diagnostic marker for ACC with adequate cell block material.…”
Section: Perspectivesmentioning
confidence: 99%